The roots of urban renaissance : gentrification and the struggle over Harlem - Goldstein, Brian D., 1982-; Sugrue, Thomas J. (Princeton, New Jersey : Princeton University Press, 2022)
An acclaimed history of Harlem's journey from urban crisis to urban renaissance. With its gleaming shopping centers and refurbished row houses, today's Harlem bears little resemblance to the neighborhood of the midcentury urban crisis. Brian Goldstein traces Harlem's Second Renaissance to a surprising source: the radical social movements of the 1960s that resisted city officials and fought to give Harlemites control of their own destiny. Young Harlem activists, inspired by the civil rights movement, envisioned a Harlem built by and for its low-income, predominantly African American population. In the succeeding decades, however, the community-based organizations they founded came to pursue a very different goal: a neighborhood with national retailers and increasingly affluent residents. The Roots of Urban Renaissance demonstrates that gentrification was not imposed on an unwitting community by unscrupulous developers or opportunistic outsiders. Rather, it grew from the neighborhood's grassroots, producing a legacy that benefited some longtime residents and threatened others.
Reforming renewal -- Black utopia -- Own a piece of the block -- The urban homestead in the age of fiscal crisis -- Managing change -- Making markets uptown -- Conclusion: Between the two Harlems -- Abbreviations -- Notes -- Appendix: Oral history transcripts.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on February 08, 2023).
JSTOR
Keywords: Gentrification -- New York (State) -- New York; Community development -- New York (State) -- New York; Neighborhood leaders -- New York (State) -- New York; Community organization -- New York (State) -- New York; African American neighborhoods -- New York (State) -- New York -- History; Harlem (New York, N.Y.) -- History; Embourgeoisement (Urbanisme) -- New York (État) -- New York; Développement communautaire -- New York (État) -- New York; Chefs de quartier -- New York (État) -- New York; Organisation communautaire -- New York (État) -- New York; Quartiers noirs américains -- New York (État) -- New York -- Histoire; ARCHITECTURE / Urban & Land Use Planning; African American neighborhoods; Community development; Community organization; Gentrification; Neighborhood leaders; New York (State) -- New York; New York (State) -- New York -- Harlem; Architects' Renewal Committee in Harlem; Harlem Commonwealth Council; Harlem Urban Development; J. Max Bond; Morningside Heights; Preservation of the East Harlem Triangle; brownstones; commercial development; gentrification; housing abandonment; low-income housing; model cities; new york state affordable housing; urban homesteading; urban renewal; History